Digital Map Soup: what's Cooking in British Academic Libraries and are we helping our Users? - Moore, John (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
My original intention had been to consider the roles being developed in British academic libraries to assist users in making full use of cartographic material that is available for their requirements - an almost predictable report on the blending of the old with the new and, again hopefully, coming to a slightly more positive vision of the future for the academic map library in the United Kingdom. That was before I received an e-mail from David Medyckyj-Scott, Research and Geo-Data Services Manager at the EDINA National Data Centre in Edinburgh and one of the key figures behind the implementation and development of the Digimap service to the UK Higher and Further Education sectors. Launched in 2000, Digimap delivers Ordnance Survey map data to subscribing institutions and allows staff and students to produce map extracts at set scales, to generate their own maps online or download map data to use with appropriate application software such as CAD or GIS. I do not think it is an overstatement to suggest that the advent of the Digimap service has been the most important and influential event in British academic map libraries in, at least, the last thirty years - and I say this as someone who was critically cautious of the service at the outset.